Solving problems in food engineering - Yanniotis, S (Springer, 2017)
Solving Problems in Food Engineering is a step by step workbook intended to enhance students' understanding of complicated concepts and to help them practice solving food engineering problems. The book covers problems in fluid flow, heat transfer, mass transfer, and the most common unit operations that have applications in food processing, such as thermal processing, cooling and freezing, evaporation, psychrometrics and drying. Included are theoretical questions in the form of true or false, solved problems, semi-solved problems, and problems solved using a computer. The semi-solved problems guide students through the solution. Some of the problems progress from elementary level increasing difficulty so that the book is useful to food science as well as food engineering students. About the Editor: Stavros Yanniotis is an associate professor of food engineering in the Agricultural University of Athens' Department of Food Science & Technology.